Degree of Approximation of Function in the Holder Metric (C 1)(e, c) Means of its Fourier Series - H. L. Rathore (International Journal of Mathematics And its Applications, 2023)
We extended a theorem of Das, Ghosh and Ray [4] obtained a result on degree of approximation of function in the Holder metric by (e, c) mean. In 2022, Rathore, Shrivastava and Mishra [13] has been determined the result on degree of approximation of a function in the Holder metric by (C, 1) F(a, q) mean of its Fourier series. Further we extend the result on degree of approximation of function in the Holder metric by (C, 1) (e, c) means of its Fourier series, has been proved.